2007
DOI: 10.1074/jbc.m702463200
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Hydrogen Peroxide Induces Iron Uptake by Transferrin Receptor-1 Independent of the Iron Regulatory Protein/Iron-responsive Element Network

Abstract: Local and systemic inflammatory conditions are characterized by the intracellular deposition of excess iron, which may promote tissue damage via Fenton chemistry. Because the Fenton reactant H 2 O 2 is continuously released by inflammatory cells, a tight regulation of iron homeostasis is required. Here, we show that exposure of cultured cells to sustained low levels of H 2 O 2 that mimic its release by inflammatory cells leads to upregulation of transferrin receptor 1 (TfR1), the major iron uptake protein. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…2B). These responses are consistent with stabilization of TfR1 mRNA and translational inhibition of ferritin mRNA by activated IRP2 [1][2][3]; the increase of TfR1 expression is also congruous with the reported IRP-independent stimulation of TfR1 mRNA translation that is elicited during mild sustained oxidative stress [28]. As the catabolism of H 2 O 2 by catalases is associated with generation of oxygen [22], the degradation of a 1 mM H 2 O 2 bolus may lead to hyperoxia, which would be expected to upregulate FBXL5 and antagonize the stabilization of IRP2.…”
Section: Discussionsupporting
confidence: 82%
“…2B). These responses are consistent with stabilization of TfR1 mRNA and translational inhibition of ferritin mRNA by activated IRP2 [1][2][3]; the increase of TfR1 expression is also congruous with the reported IRP-independent stimulation of TfR1 mRNA translation that is elicited during mild sustained oxidative stress [28]. As the catabolism of H 2 O 2 by catalases is associated with generation of oxygen [22], the degradation of a 1 mM H 2 O 2 bolus may lead to hyperoxia, which would be expected to upregulate FBXL5 and antagonize the stabilization of IRP2.…”
Section: Discussionsupporting
confidence: 82%
“…Preliminary data from ALD patients and ethanol-treated mice models sug gest that hepatic iron uptake pathways are increased in the liver and potential mechanisms involve an increase of the transferrin receptor (TfR)1 and repression of the systemic iron hormone hepcidin that controls duodenal iron absorption and RES-mediated iron release via the iron exporter ferroportin [119,120] . Using novel in vitro and in vivo models [121,122] , we have recently demonstrated that H2O2 alone increases TfR1 via posttranscriptional and translation mechanisms ultimately leading to cellular accumulation of iron [123,124] . These data show that chronic exposure of cells to non toxic levels of H2O2 lead to accumulation of iron via distinct regulatory mechanisms promoting Fenton chemistry.…”
Section: Ethanol and Hcv Lead To Hepatic Iron Accumulationmentioning
confidence: 99%
“…and catalase (CAT) were purchased from Sigma-Aldrich. Actual activities of GOX and CAT were determined at very low H 2 O 2 concentrations prior to the experiment using a sensitive chemiluminescence technique (19,22,25,26). During all experiments, k GOX was kept at 4 ϫ 10 Ϫ8 M/s, whereas k CAT was adjusted to reach defined H 2 O 2 ss concentrations between 0.15 and 6 M. Because GOX metabolizes glucose and oxygen stochiometrically to H 2 O 2 and ␦-gluconolactone, k GOX was selected to not decrease glucose levels during 24 h by more than 3 mM, which does not influence glucose metabolism.…”
Section: Cytokines and Reagentsmentioning
confidence: 99%
“…Previous studies showed direct regulatory control of iron homeostasis by H 2 O 2 ; the iron regulatory protein 1 (IRP1), which usually stabilizes the mRNA of TfR1 by binding to iron-responsive elements in the 3Ј-untranslated region (16), shows increased binding activity under persistently elevated H 2 O 2 concentrations (17,18). In addition, TfR1 is up-regulated independent of IRP-1 at the translational level under sustained levels of H 2 O 2 (19). Both pathways finally lead to an iron shift into cells and removal of circulating free iron.…”
mentioning
confidence: 99%
See 1 more Smart Citation